Pooled Antibiotic Susceptibility Testing Performs Within CLSI Standards for Validation When Measured Against Broth Microdilution and Disk Diffusion Antibiotic Susceptibility Testing of Cultured Isolates - Emery Haley; Frank R. Cockerill; Rick L. Pesano; Richard A. Festa; Natalie Luke; Mohit Mathur; Xiaofei Chen; Jim Havrilla; David Baunoch (Antibiotics)
Background/Objectives: While new methods for measuring antimicrobial susceptibility have been associated with improved patient outcomes, they should also be validated using standard protocols for error rates and other test metrics. The objective of this study was to validate a novel susceptibility assay for complicated and recurrent urinary tract infections (UTIs): pooled antibiotic susceptibility testing (P-AST). This assay was compared to broth microdilution (BMD) and disk diffusion (DD), following Clinical and Laboratory Standards Institute (CLSI) guidelines for assessment of error rates and agreement. Methods: This study analyzed consecutive fresh clinical urine specimens submitted for UTI diagnostic testing. Upon receipt, the urine samples were subjected in parallel to standard urine culture and multiplex polymerase chain reaction (M-PCR) for microbial identification and quantification. Specimens with the same monomicrobial non-fastidious bacteria detected by both M-PCR and standard urine culture (SUC) underwent standard antibiotic susceptibility testing (AST) and P-AST antibiotic susceptibility testing. Analysis was also undertaken to assess the presence of heteroresistance for specimens with P-AST-resistant and BMD/DD consensus-susceptible results. Results: The performance measures without correction for heteroresistance showed essential agreement (EA%) of ≥90%, very major errors (VMEs) of <1.5%, and major errors (MEs) of <3.0% for P-AST, all meeting the threshold guidelines established by CLSI for AST. The categorical agreement (CA%) also met acceptable criteria (>88%), as the majority of the errors were minor (mEs) with essential agreement. The very major and major error rates for P-AST decreased to <1.0% when heteroresistance was accounted for. Conclusions: The P-AST assay methodology is validated within acceptable parameters when compared to broth microdilution and disk diffusion using CLSI criteria.